PERAN PEREKONOMIAN INDONESIA DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN MELALUI INTEGRASI SDGS DAN KEBIJAKAN PUBLIK NASIONAL - Anisah Harahap; Muzayyana; Robbani hafidz Lubis; Reni Ria Armayani Hasibuan (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study examines the role and challenges of Indonesia in achieving sustainable development in line with the Sustainable Development Goals (SDGs). Sustainable development in Indonesia is not solely focused on economic growth, but also emphasizes the balance between social equity, environmental protection, and good governance. This research employs a literature review method by analyzing national academic journals and policy documents related to sustainable development in Indonesia published after 2020. The findings indicate that Indonesia has demonstrated a strong commitment to sustainable development through the integration of the SDGs into national and regional development planning frameworks. However, the implementation process still faces several obstacles, including regional disparities, environmental degradation, limited institutional capacity, and suboptimal community participation. In addition, global challenges such as climate change and economic instability further affect the achievement of sustainable development targets in Indonesia. Therefore, strengthening evidence-based policies, enhancing cross-sectoral collaboration, and utilizing innovation and technology are essential to support inclusive and sustainable development. This study is expected to contribute both academically and practically to enriching the discourse on sustainable development in Indonesia and to provide insights for policymakers and stakeholders.